Effects of fire on tree survival and regeneration in a Mediterranean ecosystem - Catry, Filipe Xavier; Rego, Francisco Castro; Bugalho, Miguel Nuno; Lopes, Tito; Silva, Joaquim Sande; Moreira, Francisco (Forest Ecology and Management, 2006)
Portugal is the only European Mediterranean country where the annual average burnt area has increased in the last two decades. Although forest ﬁres at national level annually represent very important losses, few studies evaluated the mortality and the capacity of auto-regeneration of the different tree species in burnt areas. After a wildﬁre that occurred in September 2003, we started a research project in a public protected area in central west Portugal. The main goal of this study, still ongoing, is to evaluate the post-ﬁre regeneration capacity of different tree species occurring in the country. We expect to quantify the survival/mortality rates of selected tree species in relation to variables such as ﬁre severity, tree height and diameter, and evaluate species regeneration strategies as well as their growth rates after ﬁre disturbance. In this study 667 trees from 11 species were selected for monitoring, namely: Castanea sativa, Crataegus monogyna, Eucalyptus globulus, Fraxinus angustifolia, Olea europaea var. sylvestris, Pinus pinaster, Pinus pinea, Pistacia lentiscus, Quercus coccifera, Quercus faginea and Quercus suber. Results obtained two springs after ﬁre, show that almost all broadleaved trees (9 species) survived to the ﬁre. Contrarily, the majority of coniferous trees died after the ﬁre. Despite the very low mortality observed in broadleaved trees, most of them did not regenerate from the crown, but only from the base, trunk or roots, which means that the recovering process will be much slower. Exceptions to this were cork oak and eucalyptus. Within native species, Quercus suber is by far the most resilient to ﬁre. For most part of the monitored tree species, which resprouted from the base of the trunk, Eucalyptus globulus was the one that recovered faster, followed by Fraxinus angustifolia and Quercus faginea.
Keywords: mortality; natural regeneration; post-ﬁre recovery; Tree species

Effects of fire on tree survival and regeneration in a Mediterranean ecosystem - Catry, Filipe Xavier; Rego, Francisco Castro; Bugalho, Miguel Nuno; Lopes, Tito; Silva, Joaquim Sande; Moreira, Francisco (Forest Ecology and Management, 2006)
Portugal is the only European Mediterranean country where the annual average burnt area has increased in the last two decades. Although forest ﬁres at national level annually represent very important losses, few studies evaluated the mortality and the capacity of auto-regeneration of the different tree species in burnt areas. After a wildﬁre that occurred in September 2003, we started a research project in a public protected area in central west Portugal. The main goal of this study, still ongoing, is to evaluate the post-ﬁre regeneration capacity of different tree species occurring in the country. We expect to quantify the survival/mortality rates of selected tree species in relation to variables such as ﬁre severity, tree height and diameter, and evaluate species regeneration strategies as well as their growth rates after ﬁre disturbance. In this study 667 trees from 11 species were selected for monitoring, namely: Castanea sativa, Crataegus monogyna, Eucalyptus globulus, Fraxinus angustifolia, Olea europaea var. sylvestris, Pinus pinaster, Pinus pinea, Pistacia lentiscus, Quercus coccifera, Quercus faginea and Quercus suber. Results obtained two springs after ﬁre, show that almost all broadleaved trees (9 species) survived to the ﬁre. Contrarily, the majority of coniferous trees died after the ﬁre. Despite the very low mortality observed in broadleaved trees, most of them did not regenerate from the crown, but only from the base, trunk or roots, which means that the recovering process will be much slower. Exceptions to this were cork oak and eucalyptus. Within native species, Quercus suber is by far the most resilient to ﬁre. For most part of the monitored tree species, which resprouted from the base of the trunk, Eucalyptus globulus was the one that recovered faster, followed by Fraxinus angustifolia and Quercus faginea.
Keywords: mortality; natural regeneration; post-ﬁre recovery; Tree species

Post-fire recovery of Mediterranean ground ant communities follows vegetation and dryness gradients - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Biogeography, 2006)
Aim In the Mediterranean Basin, the main forest communities vary in their ability to recover after ﬁre. In this study we analyse the effects of ﬁre on ant communities occurring in various vegetation types distributed along a geographical gradient in the western Mediterranean region. Location The study was carried out in burned and unburned habitats of 22 sites corresponding to eight vegetation types distributed along a gradient of dryness throughout Catalonia (north-east Spain). Methods We placed ﬁve pairs of plots (one plot located in the burned area and the second one placed in the unburned margin) per site. We compared ant communities in these unburned and burned plot types 8 years after ﬁre using pitfall traps. Traps were set out in mid-May and mid-July. We analysed the structure and composition of ant communities in the burned and unburned areas of these vegetation types using anova tests, correspondence analysis (CA) and linear regression. Results The resilience of ant communities varies with vegetation type. Ant communities in forests with high resilience also recover rapidly after ﬁre, while those in forests that do not recover after ﬁre show the lowest resilience. Species richness does not depend on burning or vegetation type. The resilience of these Mediterranean ant communities to ﬁre is related to the environmental characteristics of the region where they live. Accordingly, differences between burned and unburned habitats are smaller for ant communities in areas with higher water deﬁcit in summer than for those in moister ones. Main conclusions The structure and composition of ant communities after ﬁre depends on the level of direct mortality caused by the ﬁre. It affects ant species differently, as determined by the habitats used for nesting and foraging. The reestablishment of vegetation cover depends on forest composition before the ﬁre. As vegetation cover determines resource and microhabitat availability and competitive relationships among species, forest composition before the ﬁre also affects post-ﬁre recovery of ant communities to the medium-term. Finally, ant communities living in drier areas recover more quickly after ﬁre than those living in moister ones. This pattern might be because in areas with higher water deﬁcit there are more species characteristic of open environments, which are habitats similar to those generated after ﬁre.
Keywords: Ants; diversity; dryness gradient; forest type; Mediterranean communities; post-ﬁre recovery; resilience; Species richness; ﬁre

Post-fire recovery of Mediterranean ground ant communities follows vegetation and dryness gradients - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Biogeography, 2006)
Aim In the Mediterranean Basin, the main forest communities vary in their ability to recover after ﬁre. In this study we analyse the effects of ﬁre on ant communities occurring in various vegetation types distributed along a geographical gradient in the western Mediterranean region. Location The study was carried out in burned and unburned habitats of 22 sites corresponding to eight vegetation types distributed along a gradient of dryness throughout Catalonia (north-east Spain). Methods We placed ﬁve pairs of plots (one plot located in the burned area and the second one placed in the unburned margin) per site. We compared ant communities in these unburned and burned plot types 8 years after ﬁre using pitfall traps. Traps were set out in mid-May and mid-July. We analysed the structure and composition of ant communities in the burned and unburned areas of these vegetation types using anova tests, correspondence analysis (CA) and linear regression. Results The resilience of ant communities varies with vegetation type. Ant communities in forests with high resilience also recover rapidly after ﬁre, while those in forests that do not recover after ﬁre show the lowest resilience. Species richness does not depend on burning or vegetation type. The resilience of these Mediterranean ant communities to ﬁre is related to the environmental characteristics of the region where they live. Accordingly, differences between burned and unburned habitats are smaller for ant communities in areas with higher water deﬁcit in summer than for those in moister ones. Main conclusions The structure and composition of ant communities after ﬁre depends on the level of direct mortality caused by the ﬁre. It affects ant species differently, as determined by the habitats used for nesting and foraging. The reestablishment of vegetation cover depends on forest composition before the ﬁre. As vegetation cover determines resource and microhabitat availability and competitive relationships among species, forest composition before the ﬁre also affects post-ﬁre recovery of ant communities to the medium-term. Finally, ant communities living in drier areas recover more quickly after ﬁre than those living in moister ones. This pattern might be because in areas with higher water deﬁcit there are more species characteristic of open environments, which are habitats similar to those generated after ﬁre.
Keywords: Ants; diversity; dryness gradient; forest type; Mediterranean communities; post-ﬁre recovery; resilience; Species richness; ﬁre